Empowerment of Sub-Urban Community Groups to Improve Education in Waste Management Techniques in Dukuh Hamlet, Sinduharjo, Ngaglik, Sleman DIY - Sudaryatno; Agus Prasetya; Muhammad Sulaiman; Heni Wahyu Sartika; Dian Hudawan Santoso; Marjan Bato; Nurul Fadhlya Hidayatunnisa; Iga Maliga; Indro Kisnanto (Jurnal Pengabdian, Riset, Kreativitas, Inovasi, dan Teknologi Tepat Guna, 2024)
Dukuh Hamlet is one of the areas that is developing the process of managing organic and inorganic waste based on Black Soldier Fly (BSF) maggot cultivation. This is a response to the increasing volume of organic and inorganic waste at the Piyungan DIY TPA. The purpose of this community service program is to conduct socialization, coaching and ongoing assistance to community groups through the "Migunani" waste group to independently process household waste that can be used for various needs. Thus, the waste problem can be reduced and increase the economic value of the community. The method of implementing the activity is divided into 6 stages, namely: 1) preparation and licensing stages; 2) community workshops and education; 3) periodic training and assistance; 4) comparative studies at Omah Maggot Jogja; 5) distribution of waste management tools in the form of composter sacks, composter barrels and biopore drills; and 6) monitoring and evaluation stages. The results of the entire series of community service went well and smoothly. The expected results in the long term are community independence in managing organic and inorganic waste so that waste from Dukuh Hamlet does not need to be taken to the TPA. The conclusion of this program is that community groups gain increased knowledge and begin to manage waste both for maggot houses and independently in their respective homes.